Decoding the exosomal nucleic acid delivery system axis of macrophage autophagy and immune reprogramming via multi-omics analysis - Zhu, Zhoujun; Xiang, Wei; Zhang, Pengchao; Yasin, Parhat; Song, Xinghua (Frontiers in Molecular Biosciences, 2025)
BackgroundMicroRNA-155 (miR-155) is a key regulator of macrophage function, and its abnormal expression is closely associated with the pathogenesis of tuberculosis (TB)—a disease where impaired macrophage autophagy weakens anti-mycobacterial immunity. Exosomes are promising nucleic acid carriers due to their biocompatibility and cell-targeting ability. Here, we constructed exosome-based miR-155 delivery systems (Exo-miR155-ago/Exo-miR155-antago; “ago” = agomir, a miR-155 agonist that enhances its expression; “antago” = antagomir, a miR-155 antagonist that inhibits its expression) to modulate macrophage autophagy and remold anti-TB immune responses.MethodsExosomes were isolated from the supernatant of bone marrow mesenchymal stem cells using differential centrifugation. The miR155-5p agomir and antagomir were transfected into exosomes via the Exosome Transfection Kit, followed by co-incubation with macrophages. Transcriptomics and proteomics were employed to screen for differentially expressed genes and proteins. Western blot was employed to detect autophagy-related proteins and phosphorylated proteins in signaling pathways (p- denotes phosphorylation, a key post-translational modification regulating protein activity). Techniques including transmission electron microscopy (TEM), Monodansylcadaverine (MDC) staining, and reverse transcription-quantitative polymerase chain reaction (RT-qPCR) were applied to detect the autophagic level of macrophages.ResultsTranscriptome sequencing identified 704 differentially expressed genes, with significant enrichment in TNF and NF-κB pathways, differential expression of NF-κB target genes (e.g., autophagy core gene Beclin1), and expression changes in key genes of the energy metabolism-related AMPK/mTOR pathway; proteomic analysis found 164 differentially expressed proteins, including key molecules of the “Pathogen Recognition-TLR4-NF-κB-Autophagy-Related Gene Transcription” pathway (TLR4, p-p65) and core proteins of the AMPK/mTOR pathway (p-AMPK, p-mTOR); functional verification showed the Exo-miR155-ago group had more autophagosomes (TEM), higher autophagic vacuole accumulation (MDC staining), upregulated mRNA/protein of autophagy-related molecules (LC3B, Beclin1), downregulated mRNA/protein of p62 (RT-qPCR/Western blot), activated p-p65 (NF-κB pathway), and increased p-AMPK with decreased p-mTOR (AMPK/mTOR pathway), and all results confirmed Exo-miR155-ago promotes macrophage autophagy via the synergistic effect of the two pathways.ConclusionThis study provides multi-omics evidence for autophagy modulation mediated by the exosomal nucleic acid delivery system, verifies that this system regulates macrophage autophagy by controlling the TLR4-NF-κB pathway and AMPK/mTOR pathway, and clarifies the application potential of this system in tuberculosis (TB) and other macrophage-associated.